To simplify the expression \((7^3)^9\) using the Power Rule of Exponents, you multiply the exponents:
\[ (7^3)^9 = 7^{3 \cdot 9} = 7^{27} \]
So, the simplified expression is:
7^27
7 to the 27th power
.(1 point)
Responses
7^27
7 to the 27th power
7^6
7 to the 6th power
21^9
21 to the 9th power
7^12
1 answer
To simplify the expression \((7^3)^9\) using the Power Rule of Exponents, you multiply the exponents:
\[ (7^3)^9 = 7^{3 \cdot 9} = 7^{27} \]
So, the simplified expression is:
7^27
7 to the 27th power